Demographic characteristics and repeat overdose risk factors in 601 patients with intentional drug overdose in the emergency department: a cross-sectional study - Rong, Shumin; Wan, Yonghui; Zhou, Han; Zhang, Chun; Fan, Meiling; Hao, Jie; Yan, Xiaojie (Frontiers in Psychiatry, 2026)
ObjectiveTo examine the demographic and clinical characteristics of patients with intentional drug overdose (IDO) presenting to the emergency department and to identify risk factors associated with repeated IDO, thereby providing an evidence-based foundation for emergency nursing interventions and prevention strategies.MethodsA retrospective cross-sectional study was conducted using emergency department medical records of 601 patients with intentional drug overdose (IDO) (ICD-10 codes: T36–T50) who presented to a tertiary hospital in Wuhan, China, between January 2023 and December 2024. Demographic characteristics, seasonal distribution, substance categories, psychiatric history, alcohol use, and prior self-harm were collected. Descriptive statistics, chi-square tests, and multivariable logistic regression analyses were performed.ResultsThe majority of patients were female (70.4%) and adolescents or young adults aged 10–29 years (72.2%), with a median age of 22 years. Overall, IDO cases demonstrated seasonal peaks in autumn and spring, accounting for 61.6% of presentations. Age-stratified analyses revealed significant seasonal variation (χ² = 27.064, p = 0.008), with adolescents and young adults showing a pronounced autumn peak (both >35%), whereas middle-aged adults (45–59 years) exhibited a relative summer peak. Medication-related poisoning accounted for 96.7% of cases, primarily involving antipsychotics and sedative–hypnotics, while pesticide poisoning comprised 3.3%. A history of prior self-harm was independently associated with repeated IDO (OR = 26.66, 95% CI: 11.17–63.61, p < 0.001). Conclusion: Patients presenting with IDO in the emergency department were predominantly adolescents and young adults, with a higher proportion of females. Overall presentations peaked in autumn and spring, largely driven by younger age groups. A prior history of self-harm was independently associated with repeated IDO. Emergency nurses should routinely assess self-harm history, prioritize early identification and intervention among high-risk adolescents and young adults, and strengthen integrated “emergency–psychiatry–community” care pathways to reduce recurrence.